Family Communication Management to Maintain relationships among Employee at LAZ Coal Mandiri - Suntoro, Suntoro; Zulaikha, Zulaikha; Widianto, Didik Sugeng; Maella, Nurannafi Farni Syam (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Strong family ties, especially in professional settings, require open and straightforward communication. This study examines how family communication management affects employee relationships at LAZ Coal Mandiri, a major coal mining firm. Family communication affects professional behavior and relationships, according to research. Strong family communication has been shown to improve job happiness, organizational dedication, and work-life balance. This study followed Robert K. Yin's case study principles. A single-case study was used to understand LAZ Coal Mandiri's family communication management strategies. Twenty supervisors and frontline staff were asked about family communication and how it influences their work relationships.We carefully reviewed corporate records and archives to confirm interview data. This case study shows that family communication management can strengthen employee-employer relations at LAZ Coal Mandiri. Based on qualitative evidence, workers who receive family support and feel comfortable discussing work issues tend to bond with their bosses and coworkers. The case study showed how regular family reunions and honest work-life balancing chats promote success. This case study impacts HR policies and organizational management. LAZ Coal Mandiri may improve employee family communication competency by understanding the importance of family communication in employee-employer relationships. This could include family workshops, therapy, and a work-life-balanced company culture. These activities may improve employee well-being, productivity, and company unity.